Impressão 3D de compósitos de fosfatos de cálcio com poli (ácido lático) para aplicações biomédicas - Napolitano, Marcos Aurélio (Universidade Federal de São Carlos, 2017)
The present work was carried out to analyze the viability of the 3D printing technique for the production of ceramic/polymer composites with bioabsorbable characteristics and both physical-chemical and mechanical properties suitable for the production of implants with a better osseointegration potential and less invasiveness. PLA/calcium phosphate composites in different amounts of organic fillers were obtained for better understanding the application limits of the 3D printing technique through composite filament fusion. Two different routes synthesized calcium phosphate: polymer precursors and acid method. For the composites, mixtures of 10, 30 and 50% by weight of the ceramic were tested, the polylactic acid polymer (PLA) was used, and the dispersion of this hydroxyapatite (HA) was compared with the presence of a compatibilizer, maleic anhydride acid (AM). Characterization analysis, such as Infrared (FT-IV) spectroscopy, Raman spectroscopy, X-ray diffraction (XRD), Scanning electron microscopy (SEM), thermogravimetry (TGA), differential scanning calorimetry (DSC) and EDS dispersive energy spectroscopy) were used for ceramics as well as for the PLA polymer, and mechanical strength parameters analysis such as tensile, compression, shear and torsion, were also carried out in order to obtain mechanical characteristics of the obtained and studied composites. At the end of the synthesis of the ceramics, two types of calcium phosphate ceramics were obtained, and the one chosen was the one obtained through the wet process, hydroxyapatite (HA), due to its better crystallinity and purity. For mixing the ceramic and polymer, the chloroform solvent was used, due to the excellent polymer solubility and it was easily removed from the composite by evaporation. At the end of 3D printing of all composites, mechanical strength tests were performed in order to compare them with human bone data found in the literature. Preliminary testing with rats was also carried out. In conclusion, the most appropriate route of synthesis of the ceramic was found to be the wet method; The method of compatibilizing the ceramic into the polymer via dissolution with the chloroform solvent is efficient and safe. The impressions of the test specimens for mechanical tests via 3D printing are better performed with the aid of the AM, the obtained data from mechanical resistance meet the need of larger pieces for use of the composite in the medical and dentistry, and that the composite is biocompatible.
3D printing of calcium phosphates with poly (lactic acid) composites for biomedical applications
Keywords: Biomateriais; Compósito; Impressão 3D; Osseointegração; Bioabsorvível; Hidroxiapatita; Biomecânica; PLGA; PLA; β-TCP; Calcium phosphate; Bioabsorbable; Osseointegration; Hydroxyapatite; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES